Impact of Varying Levels of Physical Activity on Addictive Nature of Social-Media and its Association with Sleep Quality: A Correlational Perspective - Rehman, Abaid ul; Ali, Asif; Azam, Muhammad (Annals of Human and Social Sciences, 2024)
To study the connection between physical activity and social media addiction, and its association with quality of sleep among university students was this study’s primary goal. In contemporary times, scholars have shown a growing interest in investigating the impact of varying factors on human health. Therefore, through a quantitative research design, data was collected from 409 participants aged 18 to 25 in years. Data collection tools comprised of demographic information, IPAQ, BSMAS and PSQI. Results indicate notable levels of sedentary lifestyles (42.8%) and poor sleep quality (56.5%) alongside high rates of social media addiction (90.7%) among participants. Pearson correlation analysis revealed a positive association between physical activity and subjective sleep quality. However, increased social media addiction, particularly in the relapse component, was associated with decreased subjective sleep quality. These findings highlight the significance of holistic health interventions targeting physical activity and recommend the promotion of improved sleep outcomes among students.